The effect of policy implementation on village fund cash direct assistance services in Tagog Apu Village Padalarang District West Bandung Regency - Susilawati, Susilawati; Ramdani, Dadan; Trianti, Neneng Tria; Pebryantini, Dewi; Puli, Tri Yani (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Policy implementation is seen from the end result, namely in public services, so the purpose of this study is to determine and analyze the effect of the policy of direct village cash assistance (BLTDD) associated with distribution services to beneficiaries, with a case study in Tagog Apu Village, Padalarang District, Bandung Regency. West, West Java Province, Indonesia. Using a qualitative approach, where primary data was obtained from the results of respondents' answers, totaling 62 people responded to a questionnaire regarding the implementation of policies and services for the distribution of BLTDD, processed using Pearson correlation analysis and analysis of determination to determine the magnitude of the effect, and then a description of the results of the respondent's answers was given. of dimensions and indicators regarding implementation and public services. The results of the study indicate that the implementation of the BLTDD policy has been successful, which is indicated by the good distribution of BLTDD services to beneficiary families. The findings of this study are clarity of policy communication is the most important thing in policy implementation and openness of service procedures.